Handmade electronic music: the art of hardware hacking - Collins, Nicolas 1954- (New York Routledge, 2020)
Handmade Electronic Music: The Art of Hardware Hacking provides a long-needed, practical, and engaging introduction to the craft of makingas well as creatively cannibalizingelectronic circuits for artistic purposes. With a sense of adventure and no prior knowledge, the reader can subvert the intentions designed into devices such as radios and toys to discover a new sonic world. You will also learn how to make contact microphones, pickups for electromagnetic fields, oscillators, distortion boxes, mixers, and unusual signal processors cheaply and quickly. At a time when computers dominate music production, this book offers a rare glimpse into the core technology of early live electronic music, as well as more recent developments at the hands of emerging artists.This revised and expanded third edition has been updated throughout to reflect recent developments in technology and DIY approaches. New to this edition are chapters contributed by a diverse group of practitioners, addressing the latest developments in technology and creative trends, as well as an extensive companion website that provides media examples, tutorials, and further reading. This edition features:Over 50 new hands-on projects.New chapters and features on topics including soft circuitry, video hacking, neural networks, radio transmitters, Arduino, Raspberry Pi, data hacking, printing your own circuit boards, and the international DIY communityA new companion website at www.HandmadeElectronicMusic.com, containing video tutorials, video clips, audio tracks, resource files, and additional chapters with deeper dives into technical concepts and hardware hacking scenes around the worldWith a hands-on, experimental spirit, Nicolas Collins demystifies the process of crafting your own instruments and enables musicians, composers, artists, and anyone interested in music technology to draw on the creative potential of hardware hacking.